PENERAPAN MODEL PEMBELAJARAN PROJECT CITIZEN DALAM MATA KULIAH PENDIDIKAN KEWARGANEGARAAN : Bahasa - Andriyana; Atiek Rohmiyati (ABEC Indonesia, 2023)
Citizenship Education (PKn) is an important subject in developing civic attitudes in students. However, in practice there are still many who rely on theoretical understanding without providing practical experience to students. One of the learning models that can be applied in Civics is Project Citizen. This learning model teaches students to identify, analyze, and solve social problems through active participation in society. This study aims to explore the application of the Project Citizen learning model in Civics courses. The method used is a literature study with a qualitative approach by collecting data from relevant scientific journals, books, and online sources as well as through direct observation by conducting interviews and questionnaires. The application of the Project Citizen model in Civics can help students to understand citizenship concepts more practically and be involved in decision-making in society. This learning model can also improve social skills, critical thinking skills, and students' active participation in society. In the context of implementing the Project Citizen learning model in Civics, the active role of lecturers as facilitators and mentors is required, as well as collaboration between universities and community organizations as partners in implementing citizenship projects. Therefore, this study recommends the need to develop a Civics curriculum that integrates the Project Citizen learning model at every level of education to prepare students to become active and participatory citizens. Keywords: Citizenship Education, Project Citizen, Learning Model, Active, Participatory